Association between thrombin-activatable fibrinolysis inhibitor (TAFI) and clinical outcome in patients with unstable angina pectoris - Brouwers, Geert-Jan; Leebeek, Frank W. G.; Tanck, Michael W. T.; Jukema, J. Wouter; Kluft, Cornelis; de Maat, Moniek P. M. (Thrombosis and Haemostasis, 2003)
Decrease of fibrinolytic potential is considered to be a risk factor for arterial thrombosis. The recently described thrombinactivatable fibrinolysis inhibitor (TAFI) attenuates fibrinolysis by cleaving of the C-terminal lysine residues from fibrin, thereby inhibiting tPA mediated plasminogen activation. The role of plasma TAFI antigen (Ag) levels and gene polymorphisms in arterial thrombosis is still not elucidated. In this prospective study, the association between plasma TAFI Ag levels and the TAFI gene polymorphisms, Ala147Thr, Thr325Ile and -438A/G, with refractory unstable angina pectoris (UAP) was determined. The study population consisted of 209 patients with UAP of whom 76 were refractory and 133 non-refractory to medical treatment. In the same study population the contribution of these polymorphisms to plasma TAFI Ag levels was determined.Plasma TAFI Ag levels were significantly higher in non-refractory patients compared to refractory patients (geometric mean 114.4 and 105.6 U/dl respectively, p=0.042). Plasma TAFI Ag levels in the lowest quartile resulted in a 2.6 fold (95% confidence interval 1.2-5.9) increased risk for refractory UAP compared to plasma TAFI Ag levels in the upper quartile. The three studied TAFI polymorphisms had an independent and additive effect on plasma TAFI Ag levels. However, no significant association between the individual TAFI polymorphisms and refractiveness was observed.In conclusion, in this study population plasma TAFI Ag levels are significantly correlated with refractiveness in patients with UAP. Furthermore, all three polymorphisms contribute independently to plasma TAFI Ag levels, but not to refractiveness.Part of this paper was originally presented at the joint meetings of the 16th International Congress of the International Society of Fibrinolysis and Proteolysis (ISFP) and the 17th International Fibrinogen Workshop of the International Fibrinogen Research Society (IFRS) held in Munich, Germany, September, 2002.
Keywords: Thrombin-activatable fibrinolysis inhibitor (TAFI); gene polymorphisms; amino acid substitutions; protein levels; unstable angina pectoris